Photography in dentistry: Part IV (Object photography) - Siadat H; Mirfazaelian A (Tehran University of Medical Sciences, 2007)
Object photography in dentistry including dental instruments, models, teeth and gross specimens has some special features and needs special consideration. These objects are usualy very small, highly usually reflective and often with very bright surfaces. They need special lighting and other accessories for acceptable results. On the other hand, in laboratories and dental clinics we haven't enough time for taking photographs. The purpose of this article is to introduce the principles of object photography in dentistry.